2010
DOI: 10.1534/genetics.110.116087
|View full text |Cite
|
Sign up to set email alerts
|

Expression Quantitative Trait Loci: Replication, Tissue- and Sex-Specificity in Mice

Abstract: By treating the transcript abundance as a quantitative trait, gene expression can be mapped to local or distant genomic regions relative to the gene encoding the transcript. Local expression quantitative trait loci (eQTL) generally act in cis (that is, control the expression of only the contiguous structural gene), whereas distal eQTL act in trans. Distal eQTL are more difficult to identify with certainty due to the fact that significant thresholds are very high since all regions of the genome must be tested, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 24 publications
4
85
1
Order By: Relevance
“…Local eQTL had higher mapping scores than distant loci (Wilcoxon rank test, P = 1.7e-07). This is consistent with previous work showing that while both local and distant eQTL exist, local eQTL typically have stronger effects (Petretto et al 2006a;Mackay et al 2009;Van Nas et al 2010). A targeted search for local eQTL where we tested only the marker situated closest to a given gene revealed local eQTL at 12% of the genes tested, for a total of 1161 local eQTL (Table S5).…”
Section: Genomic Architecture Of Mrna Expressionsupporting
confidence: 89%
“…Local eQTL had higher mapping scores than distant loci (Wilcoxon rank test, P = 1.7e-07). This is consistent with previous work showing that while both local and distant eQTL exist, local eQTL typically have stronger effects (Petretto et al 2006a;Mackay et al 2009;Van Nas et al 2010). A targeted search for local eQTL where we tested only the marker situated closest to a given gene revealed local eQTL at 12% of the genes tested, for a total of 1161 local eQTL (Table S5).…”
Section: Genomic Architecture Of Mrna Expressionsupporting
confidence: 89%
“…Studies of natural variation in mice have identified a number of ''hotspot'' loci associated with trans regulation of genes and clinical traits. 18,19 One of the first reported human trans-acting eQTLs involved the KLF14 transcription factor in adipose tissue. 20 The locus associated with T2D and HDL-cholesterol levels showed a cis-acting association with expression of KLF14 and ten distal genes.…”
Section: Introductionmentioning
confidence: 99%
“…An eQTL study is based on treating expression as a quantitative trait and associating it with genetic variation. eQTL studies have been tremendously successful, and have identified many loci involved in gene regulation (Ghazalpour et al 2008;Veyrieras et al 2008;Cookson et al 2009;Farber et al 2009;Hayes et al 2009;Jiménez-Gómez et al 2010;van Nas et al 2010;Steibel et al 2011;Gaffney et al 2012;Kabakchiev and Silverberg 2013;Francesconi and Lehner 2014). However, the traditional eQTL approach has some fundamental limitations.…”
mentioning
confidence: 99%